2022
DOI: 10.1007/s11071-022-07837-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing energy dissipation in gas foil bearings to eliminate bifurcations of limit cycles in unbalanced rotor systems

Abstract: High-speed rotor systems mounted on gas foil bearings present bifurcations which change the quality of stability, and may compromise the operability of rotating systems, or increase noise level when amplitude of specific harmonics drastically increases. The paper identifies the dissipating work in the gas film to be the source of self-excited motions driving the rotor whirling close to bearing’s surface. The energy flow among the components of a rotor gas foil bearing system with unbalance is evaluated for var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Currently, the analysis for GFBs can be divided into an analysis based on linearized rotordynamic coefficients [15][16][17][18] and a nonlinear analysis [19][20][21]. Hoffmann et al [22] found that the linearized force coefficient method and the nonlinear method predicted very similar stability results.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the analysis for GFBs can be divided into an analysis based on linearized rotordynamic coefficients [15][16][17][18] and a nonlinear analysis [19][20][21]. Hoffmann et al [22] found that the linearized force coefficient method and the nonlinear method predicted very similar stability results.…”
Section: Introductionmentioning
confidence: 99%